Efficacy of press needle treatment in reducing chemotherapy-induced nausea, vomiting, and retching gastrointestinal cancer patients: A randomized controlled trial - Fenyu Liu; Rongrong Liao; Jianhong Cai; Mengru Bu; Ningjun Xu; Jin Zhou (Asia-Pacific Journal of Oncology Nursing, 2023)
Objective: Chemotherapy-induced nausea and vomiting (CINV) and retching often pose challenges in managing patients with gastrointestinal cancer. This randomized controlled trial sought to evaluate the effectiveness of press needle therapy in mitigating CINV and retching following chemotherapy. Methods: Two hundred patients with gastrointestinal cancer undergoing folinic acid, fluorouracil, and oxaliplatin (FOLFOX) chemotherapy were randomly assigned to either the press needle group or the control group. The control group received 5-hydroxytryptamine-3 (5-HT3) antagonists and dexamethasone 30 min before chemotherapy, followed by dexamethasone on days 2 and 3 after chemotherapy. In contrast, the press needle group received press needle treatment 30 min prior to chemotherapy. The primary outcome was the Index of Nausea, Vomiting, and Retching (INVR), assessed at seven time points: before chemotherapy and at 12, 24, 36, 48, 60, and 72 h post-chemotherapy. Results: All patients completed their respective treatments, and no significant adverse effects related to press needle treatment (such as skin allergies, acupoint infections, headaches, or dizziness) were reported. A two-way repeated-measures analysis of variance (ANOVA) revealed significant differences in INVR scores between the two groups (P < 0.05). Further analysis with a t-test indicated that INVR scores in the press needle treatment group were significantly lower than those in the control group at 12, 24, and 36 hours after chemotherapy (P < 0.05), with no significant difference observed thereafter. Conclusions: Press needle treatment effectively alleviated nausea, vomiting, and retching in patients with gastrointestinal cancer undergoing chemotherapy. It represents a safe, efficient, and convenient complement to preventive treatment with 5-HT3 antagonists. Trial registration: Chinese Clinical Trial Registry (No. ChiCTR1900024554).